MEMBANGUN KINERJA MELALUI PENGEMBANGAN KOMITMEN GURU DI KOTA SEMARANG - -, Nurhayati (VALUE ADDED | MAJALAH EKONOMI DAN BISNIS, 2011)
This study aims to analyze the performance of Primary School teachers in the city of Semarang. This study uses the variables of organizational culture, job satisfaction, and commitment to analyze the influence of teacher performance. In addition, studies using this type of research that is in use is the